1997
DOI: 10.1055/s-2008-1035012
|View full text |Cite
|
Sign up to set email alerts
|

Tyndallometrie und Zellzahlmessung in der Vorderkammer bei Amotio retinae

Abstract: Our results demonstrate a breakdown of the blood-ocular barriers in eyes with retinal detachment and an elevation of corpuscular elements in aqueous as manifestations of pseudouveitis. In eyes with PVR the alteration of blood-ocular barriers seems to be more extensive than in eyes without PVR indicating a possible role of the LFCM for early detection of PVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…Consequently, we can assume that the extent of the blood-retinal barrier disruption is associated with the extent of retinal detachment. Similar findings are shown by other studies, 9,[16][17][18] which found a correlation between the extension of the retinal detachment and the tyndallometric values. However, the studies feature few patient numbers or define the extent of retinal detachment only sparingly.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, we can assume that the extent of the blood-retinal barrier disruption is associated with the extent of retinal detachment. Similar findings are shown by other studies, 9,[16][17][18] which found a correlation between the extension of the retinal detachment and the tyndallometric values. However, the studies feature few patient numbers or define the extent of retinal detachment only sparingly.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the inclusion of only RRD patients is a limitation of this study. Care must be taken in extrapolating the results to T2DM patients and controls without RRD since the blood-retinal barrier may be disrupted to varying degrees in RRD[49,50]. Furthermore, our results concerning free AGEs and α-dicarbonyls should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Die Untersuchungseinheit erlaubt eine exakte und reproduzierbare Messung des Proteingehaltes im Kammerwasser in vivo durch Messung der Streuung eines in die Vorderkammer gescannten He-Ne-Laser-Strahles mit einem Photomultiplier [13,23]. Details der Methodik, ihre Reproduzierbarkeit sowie ihre Anwendung bei einem breiten Spektrum von Augen-und Allgemeinerkrankungen sind in einer gröûeren Zahl von Publikationen unserer und anderer Arbeitsgruppen belegt [1,13,15,17,19,20,23]. Die Messungen wurden von insgesamt vier mit dem Untersuchungsgerät gut vertrauten ¾rzten durchgeführt, jeweils fünf Einzelmessungen wurden gemittelt.…”
Section: Patienten Und Methodenunclassified